PP-49 Population pharmacokinetics and dosing optimisation of cefoperazone in children. Issue 10 (20th September 2017) - Zhao,
Abstract : Background: Cefoperazone is used in children with sus-pected or documented Gram-negative serious infections. Currently, its use is off-label partly because of lack of phar-macokinetic studies. Our aim was to evaluate the pop-ulation pharmacokinetics of Cefoperazone in children between 2–12 years of age and define the appropriate dose in order to optimise cefoperazone treatment in this vulnerable population. Methods: Blood samples were collected from children treated with Cefoperazone and concentrations were quantified by HPLC-MS. Population pharmacokinetic analysis was performed using NONMEM software. Results: The data from 83 children (age range: 2.2–10.8 years) were available for population pharmacokinet-ic analysis. A two-compartment model with first-order elimination showed the best fit with the data. A covariate analysis identified that current weight had a significant impact on cefoperazone pharmacokinetics. Conclusion: The population pharmacokinetics of Cefop-erazone was evaluated in children between 2–12 years old and an evidence-based optimal dosing regimen was established based on simulation.